2000
DOI: 10.1258/0022215001905779
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-pathological correlation between allergic rhinitis and bronchial asthma

Abstract: A prospective study was carried out on 52 patients with allergic rhinitis, during March 1993-January 1995. This was to analyse the occurrence of bronchial asthma among them and to correlate the symptoms, signs and pathological findings of allergic rhinitis with that of bronchial asthma in those patients with both the disorders. The therapeutic benefits with regard to the symptoms of bronchial asthma in these patients were assessed after treatment of their nasal allergy for a period of at least four months. A d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
1
8
1
Order By: Relevance
“…Housewives are most commonly affected (30.3%), and students are second (23.0%). Similar study done in Bangladesh showed student to be most affected (38%) and housewives secondly (30% 12 , including asthma 13,14 . We have seen that allergic conjunctivitis (18.6%) is the common co-morbid condition similar to other study which showed allergic conjunctivitis (13%) 15 and sinusitis (8.9%) is of the second in percentage.…”
Section: Discussionsupporting
confidence: 69%
“…Housewives are most commonly affected (30.3%), and students are second (23.0%). Similar study done in Bangladesh showed student to be most affected (38%) and housewives secondly (30% 12 , including asthma 13,14 . We have seen that allergic conjunctivitis (18.6%) is the common co-morbid condition similar to other study which showed allergic conjunctivitis (13%) 15 and sinusitis (8.9%) is of the second in percentage.…”
Section: Discussionsupporting
confidence: 69%
“…This fi gure is much lower than that of Verghese [21] (69%) In our study the mean age of children suffering from sinusitis was 8.9 years (SD=4.11). The onset of symptoms indicating sinusitis in these patients was between 2-4 years prior to presentation.…”
Section: Discussioncontrasting
confidence: 69%
“…As shown in Table IV, family history of allergy or asthma was present in 44.62% children against 76.9% reported by Verghese [21]. …”
Section: Discussionmentioning
confidence: 73%
“…[9,10], an early and rigorous diagnostic approach is essential, also in cases of minimal rhino-sinusal district alterations.…”
Section: Introductionmentioning
confidence: 99%